Doctor appointment booking system / Muhammad Juwaidi Muhar - Muhar, Muhammad Juwaidi (2017)
Managing patient booking record is a routine process for clinic. Conducting the process manually require patient to make a call, wait for approval and confirm booking. Since there is increasing number of patient, processing of multiplying number of booking is time consuming and require more manpower. Therefore, the computerized system was purposed to help Dr. Len clinic to handle appointment booking in more systematic way. The system is called Doctor Appointment Booking System (DABS) and was developed based on System Development Life Cycle (SDLC). The model has requirement gathering, design, coding, testing, deployment and maintenance. DABS was tested by 30 respondent and 3 expert users. Overall, the highest mean is 4.2 (SD=0.61) for user interface evaluation. In the future, the system can be enlarged to include complete module where user can choose the doctor based on their preference depend on doctor availability.